Spain : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that economic growth in Spain has resumed, and unemployment is falling. Exporters are gaining market share, and the current account is in surplus for the first time in decades. Financial conditions have improved sharply, with sovereign yields at record lows. Business investment is rebounding strongly and private consumption has also started to recover owing to improved employment prospects and rising confidence. Executive Directors have welcomed the improving Spanish economy. They have stressed that labor market reform should be accompanied by product and service market liberalization to maximize the gains to growth and jobs.